Spline approach to the solution of Sturm - Liouville problem - S., Mehrkanoon; Suleiman, Mohamed; Abdul Majid, Zanariah; S., S Chaharborj (Hikari Ltd, 2009)
This study investigates the eigenvalues of regular Sturm-Liouville problem. A quintic spline function is used to develop a numerical method for approximating the eigenvalues of Sturm-Liouville problem. We show that the approximate solutions which are obtained by the present method are better than the conventional methods given in the references. Two problems have been solved. numerical results are tabulated to illustrate the efficiency and accuracy of the present method.